311Effective prospective study sampling from an existing large-scale national survey using propensity score methods. (2nd September 2021) - Stanley, James; Harris, Ricci; Cormack, Donna; Waa, Andrew; Edwards, Richard
Abstract: Focus of Presentation: Cohort study recruitment can be complex, often requiring extensive pre-screening to recruit sufficient numbers of exposed and unexposed participants. We discuss a prospective study of the impact of racism on adult health in New Zealand (NZ), with emphasis on propensity-score based sampling and recruitment methods accessing participants from a national survey (NZ Health Survey 2017/18, n = 12, 530 eligible adults). Discussion will cover sampling design, response rate, and confounder balance in the final sample. Key empirical results will be summarised. Findings: The NZHS provided a sampling frame with complete baseline exposure and covariate data, giving n = 2, 099 exposed individuals (reported racial discrimination on NZHS). A propensity-score model (stratified by ethnicity) allowed invitation of unexposed individuals balanced on key sociodemographic confounders. Recruitment used postal invitations with telephone follow-up: individuals could respond by paper survey, online questionnaire or telephone interview. Response rate was 54%, with comparable rates in exposed/unexposed individuals, with key sociodemographic factors well-balanced by exposure status. Conclusions/Implications: Racism is an important determinant of health inequity, with limited prospective research in New Zealand. Our approach enabled appropriate recruitment from a sampling frame with baseline exposure status (NZHS), including allowance for exposure variability by ethnicity. Propensity-score matching on baseline covariates allowed for balance on key confounders at invitation, with balance maintained in the final sample. Key messages: Secondary sampling from large national surveys can provide efficient recruitment for prospective studies. We achieved a highly satisfactory response rate, and propensity-score based sampling substantially balanced confounders between exposed and unexposed groups, enhancing study validity.